2018
DOI: 10.1371/journal.pmed.1002666
|View full text |Cite
|
Sign up to set email alerts
|

High-risk human papillomavirus status and prognosis in invasive cervical cancer: A nationwide cohort study

Abstract: BackgroundHigh-risk human papillomavirus (hrHPV) infection is established as the major cause of invasive cervical cancer (ICC). However, whether hrHPV status in the tumor is associated with subsequent prognosis of ICC is controversial. We aim to evaluate the association between tumor hrHPV status and ICC prognosis using national registers and comprehensive human papillomavirus (HPV) genotyping.Methods and findingsIn this nationwide population-based cohort study, we identified all ICC diagnosed in Sweden during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
51
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 29 publications
(36 reference statements)
6
51
0
Order By: Relevance
“…It is an attractive idea that another screen at 75 or 80 years in those who have not had 3 normal prior to 65 years might detect the interval cancers from persistent HPV. It should be noted, however, that an HPV infection may become undetectable at a late stage of the oncogenic process [22]; an observation supported by our data where the old age peak in cervical cancer incidence was not reflected in the HPV-prevalence pattern. At present, Danish women exit the regular screening program at age 60-64 with an HPV-test.…”
Section: Discussionsupporting
confidence: 84%
“…It is an attractive idea that another screen at 75 or 80 years in those who have not had 3 normal prior to 65 years might detect the interval cancers from persistent HPV. It should be noted, however, that an HPV infection may become undetectable at a late stage of the oncogenic process [22]; an observation supported by our data where the old age peak in cervical cancer incidence was not reflected in the HPV-prevalence pattern. At present, Danish women exit the regular screening program at age 60-64 with an HPV-test.…”
Section: Discussionsupporting
confidence: 84%
“…This correlation between age and the likelihood of detecting HPV in cervical cancer is consistent with other international studies . In a 2018 analysis of 693 cervical cancers in the United States, HPV‐negative cancers were more likely to be poorly differentiated and to be metastatic at presentation, and were associated with poorer survival .…”
Section: Impact Of Age On Hpv Detectionsupporting
confidence: 86%
“…In a 2018 analysis of 693 cervical cancers in the United States, HPV‐negative cancers were more likely to be poorly differentiated and to be metastatic at presentation, and were associated with poorer survival . Similarly, a nationwide population‐based study in Sweden found poorer survival rates in HPV‐negative cancers in 2845 cervical cancers diagnosed at older ages, of a later stage at diagnosis and associated with poorer educational status, and were less likely to be detected through cervical cytology screening …”
Section: Impact Of Age On Hpv Detectionmentioning
confidence: 99%
“…Our findings should be carefully considered when applying HPV16/18 genotyping as a triage testonly approximately a third of HSIL+ in the older women was attributed to these types. Furthermore, in a large retrospective study approximately 20% of invasive cervical cancers were HPV negative [41], while 10% HSIL+ lesions in the oldest age group were also hrHPV negative here. These findings should be taken into consideration when shifting to HPVbased screening with the majority of screening-age population still being unvaccinated.…”
Section: Discussionmentioning
confidence: 47%